A Comparison of Cell Salvage Strategies in Posterior Spinal Fusion for Adolescent Idiopathic Scoliosis. Issue 1 (February 2015) - Carey, Paul A.; Schoenfeld, Andrew J.; Cordill, Ronda D.; Tompkins, Bryan J.; Caskey, Paul M.
<x xml:space="preserve">Abstract</x> Study Design: Retrospective case-control study. Objective: To compare the efficacy of 3 blood management strategies in patients undergoing posterior spinal fusion (PSF) for adolescent idiopathic scoliosis (AIS) in reducing donor blood transfusion. Summary of Background Data: Although intraoperative cell salvage and predonated banked blood may be effective in reducing donor blood transfusion in the perioperative period, the optimal blood management strategy is unclear. A combined cell salvage strategy holds several potential advantages but has not yet been investigated. Methods: Patients who underwent isolated PSF for AIS (n=167) were subdivided into 3 groups by perioperative blood management strategy: (1) intraoperative retransfusion of shed blood (cell saver) and predonated autologous banked blood (n=51); (2) cell saver alone (n=33); and (3) combined cell saver and postoperative collection and retransfusion of drained blood (Retransfusion drain) (n=83). Data collected included age, sex, diagnosis, body weight, number of levels fused, operative time, intraoperative and postoperative blood loss and retransfusion, preoperative and postoperative (72 h) hemoglobin and hematocrit (Hct), and amount of autologous and donor blood transfused in the perioperative period. Results: Fewer patients in the cell saver and predonated blood (3.9%) and cell saver and retransfusion drain (1.2%) groups received donor transfusions than did those managed with cell saver alone (33%). There was no significant difference in the donor transfusion rate between cell saver/predonated blood and retransfusion groups. Mean postoperative Hct (72 h) was higher in the retransfusion group 3 than in the other 2 (group 3: 29.3%, group 1: 25.4%, group 2: 26.1%). There was no significant difference in the mean change in hemoglobin and Hct after surgery between the 3 groups. Conclusions: The present study demonstrates the efficacy of a combined intraoperative and postoperative cell salvage strategy in PSF for AIS, significantly reducing perioperative donor blood transfusions, maintaining physiological Hct, and conserving blood bank resources.